NEUROLEPTIC ACTIVITY OF 5-N, N-DIETHYLSULFAMOYL-3-METHOXYPHENYLANTHRANYLIC ACID SODIUM SALT - Grygoryeva, L.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Neuroleptic activity and acute toxicity of 5-N, N-diethylsulfamoyl-3-methoxyphenylanthranylic acid sodium salt (conditional name Methsulfenylate) were studied in experiments with Wistar rats and white mice. Methsulfenylate was found to affect spontaneous, vertical and horizontal motions, orientation response, has myorelaxing effect, destroys motion coordination, exponentiates the effect of narcotic drugs, reduces phenaminic stereotypes, exerts a cataleptogenic effect, prolongs latent period of appearance of defensive avoidance conditional reflex, as well as increases the threshold of emotional reactions in laboratory animals. Acute toxicity of Methsulfenylate was 2,3 times smaller than that of aminazine.